Penguatan Literasi Keuangan Bagi Guru SDN Bajur 3 Desa Bajur, Kec. Waru, Kab. Pamekasan: Upgrade Pemahaman Keuangan Sebagai Pendidik dalam Mencetak Generasi Emas - Septiana, Aldila; Mariatun, Ika Lis; Arisinta, Octaviana; Tarman, Manah (Welfare : Jurnal Pengabdian Masyarakat, 2024)
Financial literacy is an understanding that includes matters relating to money management and its use in improving welfare. This activity to strengthen financial literacy aims to broadly upgrade individuals in dealing with finances and ultimately be able to prepare the next golden generation. The material provided is: basic concepts, benefits, indicators, and tips on financial literacy. With a method in the form of a Participatory Learning and Action (PLA) approach or a participatory learning and practice process. The results of the service show that activities to strengthen financial literacy for teachers at SDN Bajur 3, Bajur Village, Kec. Waru, Kab. Pamekasan: upgrading financial understanding as an educator in creating a golden generation is seen as providing a new understanding that can be implemented for oneself and students. It can be seen that there is a double benefit for teachers as individuals who need to upgrade their financial understanding and teachers as educators in creating a golden generation in the future. It is true that teachers as educators can educate students in terms of financial understanding, but quite a few make financial decisions far from financial rationality.